Islam's vision of extremist thought Media and antiquities as an example - Musara'a Abbas; Bahjat Abdullah (University of Mosul-college of Basic Education, 2024)
The Islamic religion has been characterized by moderation, justice, and balance in all affairs concerning man, whether spiritual or physical. Many prophetic verses and hadiths have indicated this, and therefore the Islamic religion has been in a constant struggle with extremism and extremism on the one hand, and with decadence, laxity, and escaping restrictions on the other hand. Because extremism always goes against what this religion and its goals wanted. This research dealt with Islam’s vision of extremism on the one hand, and comparing its vision with the extremist vision of the media and antiquities on the other hand.